AIAA SCITECH 2022 Forum 2022
DOI: 10.2514/6.2022-0151
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on Influence of Fuselage on Multirotor Wake Vortex Structures in Forward Flight

Abstract: With the increase interest in utilizing multirotor UAS in very low altitude airspace, the safety aspect associated with higher UAS density gains importance. One of the safety consideration is the separation requirements for UAS sharing the airspace, which consists of two major components: wake-based and CNS performance-based. To evaluate the wake-based separation requirements, the wake-field produced by the leading UAS and the resulting encounter response by the follower UAS must be obtained. While previous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Comparing to helicopters, current generation of small multirotor UAS generally utilize fixed-pitch propeller with variable speed motors; larger passenger carrying multirotor, on the other hand, could include variable pitch propeller in their design [21,22]. Experimental and simulation studies have shown inter-rotor gap could significantly affect the overall lift generation by quadrotors [23][24][25], though the propeller-to-propeller interaction appears to be reduced when an appropriately sized vehicle fuselage is included [26,27]. When in forward flight, studies have shown that the wake generated by the forward propeller pair in quadrotors would be ingested by the rear propeller pair (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing to helicopters, current generation of small multirotor UAS generally utilize fixed-pitch propeller with variable speed motors; larger passenger carrying multirotor, on the other hand, could include variable pitch propeller in their design [21,22]. Experimental and simulation studies have shown inter-rotor gap could significantly affect the overall lift generation by quadrotors [23][24][25], though the propeller-to-propeller interaction appears to be reduced when an appropriately sized vehicle fuselage is included [26,27]. When in forward flight, studies have shown that the wake generated by the forward propeller pair in quadrotors would be ingested by the rear propeller pair (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar process was also used in Refs. [32] and [27] to investigate the long-term evolution and impact of fuselage model inclusion, respectively. The simulations were carried out in two parts, the RANS turbulence modeling for near-field wake generation and the LES turbulence modeling for far-field wake generation.…”
Section: Simulation Setupmentioning
confidence: 99%